2014
DOI: 10.1007/s00405-014-2945-2
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset laryngomalacia: case reports and review of management

Abstract: Laryngomalacia is a dynamic airway condition characterised by inward collapse of flaccid supraglottic structures during inspiration. Although the most common cause of stridor in the paediatric population, adult-onset laryngomalacia remains a rare entity and its management, challenging. Two cases of adult-onset laryngomalacia are reported. A review of the English literature is performed and additional publications identified by hand-searching relevant papers; 13 case reports/series comprising 28 cases of adult-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…In view of the clinical picture of endoscopic finding of short aryepiglottic fold with long epiglottis and multiple failed attempts of extubation surgery was planned in the present case. Hey et al reported adult onset laryngomalacia in 2 patients [18] , Hyodo et al reported adult onset layngomalacia in a 20 year old female [19] and in this study we report the same in 12 year old male patient. Richter et al also reported a series of late onset laryngomalacia where 17 patients were diagnosed as having laryngomalacia when they were older than 2 years(mean age at onset 6.6 years) [20] .…”
Section: Discussionsupporting
confidence: 69%
“…In view of the clinical picture of endoscopic finding of short aryepiglottic fold with long epiglottis and multiple failed attempts of extubation surgery was planned in the present case. Hey et al reported adult onset laryngomalacia in 2 patients [18] , Hyodo et al reported adult onset layngomalacia in a 20 year old female [19] and in this study we report the same in 12 year old male patient. Richter et al also reported a series of late onset laryngomalacia where 17 patients were diagnosed as having laryngomalacia when they were older than 2 years(mean age at onset 6.6 years) [20] .…”
Section: Discussionsupporting
confidence: 69%
“…7,8 Laxity of the epiglottis is commonly discussed in the pediatric literature as one of the possible presentations of congenital laryngomalacia 9 ; however, the adult form is a rare entity that has not been well described. 10 The majority of reported cases are secondary to neurological injuries, head and neck surgery, or trauma. [11][12][13][14] Epiglottis collapse during sleep has been estimated to occur in around 12% of adult patients with OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Positional therapy seems to offer good results 28 , and epiglottidectomy has been reported to provide the most effective solution to treat epiglottis collapse 29 . Further, the high occurrence rate of epiglottis collapse in patients with OSA can partially explain the residual AHI in these patients after multi-level surgery, which usually does not include procedures for the epiglottis 30 .…”
Section: Discussionmentioning
confidence: 99%